The Domestication of Equidae in Third-Millennium BCE Mesopotamia - Juris Zarins; Rick Hauser (Les Carnets de l’ACoSt)
It has been forty years since the first edition of this book, as an Oriental Institute doctoral dissertation, was completed. Now, in a fully revised and much expanded study, CUSAS 24 presents a comprehensive discussion of the philological, historical, and archaeological evidence for the range of equidae known now from much of Western